Narratives of lives of women who breastfed their adoptive children - Suellen da Rocha Lage; Inês Maria Meneses dos Santos; Isis Vanessa Nazareth (Rev Rene)
This is a qualitative, descriptive study aiming at analyzing the experiences of women who breastfed their three adoptive children in Rio de Janeiro, RJ, Brazil. The life narrative method was used. Data collected through interviews and socioeconomic instrument in August and September 2012. Maternal age ranged from 41-57 years; the age of the child ranged from 14 hours to four days. Breastfed children ranged from four months to 1 year and 11 months of age. Two categories emerged from this thematic analysis: the paths of the adoption and the experience of the process of breastfeeding of the adoptive child. The possibility of breastfeeding was clarified to the possible adoptive mothers and they are significant; it is the health professionals´ task to encourage this practice.